Multi-omics reveals the microbial succession-driven metabolic regulation during sequential fermentation of fresh Spirulina - Kerui Su; Ayesha Shahid; Bingyu Shi; Anqi Zhao; Farouk Kamel EI-Baz; Sami I. Ali; Mohammad Asraful Alam; Muhammad Aamer Mehmood; Shenglei Bi; Shuai Yang; Jingliang Xu (International Journal of Food Microbiology, 2026)

Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Hydrogen bonding implications on sweetness behavior of sugar alcohols in food model systems: A thermophysical and FTIR study - Uzma Shahazidy; Muhammad Asghar Jamal; Muhammad Imran; Muhammad Fakhar-e-alam; Arshad Ali (Food Research International, 2026)

Prevalence and cow-level risk factors for mild and severe subclinical mastitis in intensive and extensive dairy systems in Bangladesh - Muhammad Aktaruzzaman; M. Ariful Islam; Solama Akter Shanta; Mst. Tahomina Akter; Muhammad Tofazzal Hossain; Md. Nazmul Islam; Md. Shaffiul Alam; A. K. M. Anisur Rahman (Veterinary Research Communications, 2026)

Climatic suitability and geospatial assessment of Black Soldier Fly Larvae (BSFL) for sustainable waste management - Muhammad Salam; Sami Ullah; Fakhri Alam; Camila Rodríguez-Ortega; Samia Elouali; Viola Vambol; Shafi'u Adamu; Viviana Bolletta; Faisal Hayat; Zhiyong Han (Environmental Development, 2026)

Genetic variation of grey pomfret Pampus cinereus along the Bangladesh and Malaysia coastlines with phylogeography in the Indo-West Pacific based on mitochondrial COI and Cyt β - M.M. Mahbub Alam; Md. Moshiur Rahman; Jayed Mahbub Aomio; Nur Asma Ariffin; Mohammad Asmat-Ullah; Shamima Nasren; Sarker Mohammed Ibrahim Khalil; Md. Abdullah-Al Mamun; Muhammad Anamul Kabir; Ahasan Habib (Ecological Genetics and Genomics, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Disrupting virulence: in silico discovery of MexL inhibitors to block pyocyanin biosynthesis in Pseudomonas aeruginosa - Usama Bin Asghar; Irfa Asghar; Samavia Akhter; Muhammad Ibrash Khan; Syeda Zurriat Fatima; Tatheer Alam Naqvi; Maria Kanwal Ali; Raza Ahmad; Muhammad Ali (Archives of Microbiology, 2026)

Methotrexate Loaded Polymeric Patches with Penetration Enhancers for Transdermal Delivery: in vitro, Ex Vivo, and in Vivo Characterization - Muhammad Shahid Latif; Asif Nawaz; Muhammad Khurshid Alam Shah; Muhammad Fareed; Muhammad Waseem Khan; Muhammad Luqman Nordin; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

Evaluation of Chitosan-Methotrexate Nanoparticles Loaded in Alginate Beads for Controlled Drug Delivery Against Breast Cancer - Abdullah Khan; Muhammad Fareed; Muhammad Khurshid Alam Shah; Asif Nawaz; Muhammad Faisal Shahzad; Muhammad Fauzi Abd Jalil; Zarif Mohamed Sofian; Muhammad Luqman Nordin (Journal of Pharmaceutical Innovation, 2026)

Ecological and human health risks from railway-associated contaminants: a case study of trace metal and PAH pollution along a commuter line in Chittagong, Bangladesh - Mahbub Alam; Md. Samrat Mohay Menul Islam; Muhammad Abu Bakar; Md. Ashraful Islam; Suman Das; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Hasan Mahmud Babu (Environmental Geochemistry and Health, 2026)

Mapping the evolution of green investment research: a bibliometric, dynamic topic, and SDG-based analysis of macroeconomic policy, governance, and credit - Gangyi Liao; Lim Thye Goh; Muhammad Aizat Zainal Alam (Environment, Development and Sustainability, 2026)

Probiotics unveiled: bridging general health benefits to the era of precision medicine - Mati Ullah; Muhammad Rizwan; Muhammad Ihtesham Waheed; Muhammad Shoaib Alam; Sami Ullah Jan; Ali Raza; Muhammad Faisal Shahid; Vivian Andoh; Yong Chen (World Journal of Microbiology and Biotechnology, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Decarbonizing Pakistan's cement sector: Multi-scope emissions inventory, drivers, and mitigation pathways - Unib Arshad Lodhi; Qurratulain; Muhammad Badar Alam; Muhammad Fahim Khokhar (Journal of Cleaner Production, 2026)

Assessing reach and perceptions of hygiene behaviour change interventions for people with disabilities and older adults: Multi-country matched cross-sectional study - Kazy Farhat Tabassum; Dewan Muhammad Shoaib; Md. Assaduzzaman Rahat; Mehedi Hasan; Dani Barrington; Ben Tidwell; Lauren D'Mello-Guyett; Anjali Sharma; Sheillah Simiyu; Ismail Hosen; Jenala Chipungu; Fachruddin Mangunjaya; et al. (International Journal of Hygiene and Environmental Health, 2026)

Host-derived Probiotics Enhance Immune Response and Gut Microbiome in the Freshwater Prawn Macrobrachium rosenbergii - Ayesha Akhter Sumona; Md. Belal Hossen; Saima Binte Hadi; Md. Amdadul Haque; Md. Nurul Haider; Muhammad Tofazzal Hossain; Md Samsul Alam (Probiotics and Antimicrobial Proteins, 2026)

Mangrove Ecosystem Carbon Stocks: Insights from Setiu Lagoon, Malaysia - Mohammad Ahsanul Islam; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Md Masum Billah; AFM Arifur Rahman; Muhammad Shariefuddin Bin Mohd Sukeri; Md Khurshid Alam Bhuiyan (Estuaries and Coasts, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Rational Design of SFT-Based Hole Transport Materials with Diversified Terminal Acceptors for Efficient Perovskite Solar Cells: A DFT Study - Aqsa Laraib; Tazeem Fatima; Shumaila Shaheen; Natasha Anwar; Muhammad Imran; M. Fakhar-e-Alam; Nabeel Shahzad (Journal of Fluorescence, 2026)

A novel coffee-leaf bio-lure extracted using NADES for attracting Conopomorpha cramerella - Sylvia Sjam; Ade Rosmana; Gemini Alam; Vien Sartika Dewi; Shin-ichi Tebayashi; Muhammad Agung Wardiman; Nur Azizah Fitriyanti (International Journal of Tropical Insect Science, 2026)

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Ambient ozone pollution degrades rice grain nutritional quality and straw feed value under field conditions in Bangladesh - Rigyan Gupta; Muhammad Shahedul Alam; Shamsul H. Prodhan; Kamrul Islam; Shamsun Nahar Begum; Md. Nurealam Siddiqui; Mirza Mofazzal Islam; Md Ashrafuzzaman (Environmental Pollution, 2026)

Genotypic Characterization of Genetic Diversity for the Development of Leaf Rust Resistance in Bread Wheat using SSR Markers - Mueen Alam Khan; Muhammad Farooq Naseer; Jafarov Valeh; Hafiz Ghulam Muhu Din Ahmed; Beena Alam; Adel A. Rezk; Nora M. Al Aboud (Plant Molecular Biology Reporter, 2026)

Correction: Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2026)

Integrated BIM-GIS and finite element-based framework for building planning and design - Aaqib Najeeb; Zili Zhang; Muhammad Arsalan Khan; Kong Fah Tee; Taimoor Shehzad; Abid Ali Shah; Zeshan Alam (Innovative Infrastructure Solutions, 2026)

Computational exploration of Aegle marmelos coumarins: DFT, molecular docking, and dynamics studies for anti-hypertensive activity - Jan Alam; Muhammad Ali Versiani; Nadeem Ahmed; Syed Intasar Husain Taqvi; Syed Tahir Ali; Zaheer Ul-Haq (Natural Product Research, 2026)

Transplantation of Ru265-treated mitochondria enhances the therapeutic impact on skeletal muscle ischemia-reperfusion injury - Saima Barki; Fazal Wahid; Shafia Khan; Laiba Tariq Abbasi; Zarrish Rubab; Ameer Hamza; Farman Ullah; Khadeeja Ahsan; Durre Shehwar; Muhammad Rizwan Alam (Molecular and Cellular Biochemistry, 2026)

Genetic basis of breed variation: Genome wide selection signature of neighboring sheep breeds - Muhammad Ibrahim; Muhammad Yaqoob; Mehmood Alam Khan; Irfan Ullah Wazir; Meshari Mohsen Alwazae; Sohail Ahmad (Small Ruminant Research, 2026)

The impact of acute normovolemic hemodilution on blood transfusions in cardiac surgery: a GRADE-assessed systematic review and meta-analysis of 30 randomized controlled trials with trial sequential analysis - Umama Alam; Shree Rath; Muhammad Ansab; Fazia Khattak; Hafiza Tooba Siddiqui; Muhammad Burhan; Abdul Moiz; Vishma Sabir; Zarar Ahmad Khan Afridi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correlation of tree stem diameter with root architecture, mechanical properties, and slope stability in a mountainous Cryptomeria plantation - Mehtab Alam; Jianfeng Chen; Usama Ayub; Umar Muhammad (Journal of Mountain Science, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

Root inoculation with Trichoderma harzianum primes metabolic and stress-response pathways underlying growth and resistance in Brassica rapa - Bilal Ahmad; Aleena Alam; Sohail Abbas; Muhammad Ameer Hamza; Khalid Ali Khan; Hamed A. Ghramh; Raul Narciso C. Guedes; Qiyun Li; Rizhao Chen (Pesticide Biochemistry and Physiology, 2026)

Performance assessment of nature-based solutions for sustainable urban housing - Muhammad Aarish Shah; Syed Hassaan Ali Shah; Omama Zeb; Aman Alam (Energy and Buildings, 2026)

Aqueous phase recirculation in hydrothermal liquefaction: A critical review - Ayaz Ali Shah; Muhammad Ilyas Khan; Altaf Alam Noonari; Abdul Sattar Jatoi; Judit Sandquist (Biomass and Bioenergy, 2026)

Involvement of the PD-1 pathway in the modulation of immune responses during allergic diseases - Asma’a Hassan Mohamed; Rithab Ibrahim Al-Samawi; Mohammad Chand Jamali; Sana Abdul-Jabbar Ali; Ayyub Ali Patel; Alam Eldin Musa Mustafa; Abdulrahman Samir Khairallah; Nasrin Mansuri; Ashit Kumar Dutta; Muhammad Zulfiqah Sadikan; Zaid H. Mahmoud (Inflammation Research, 2026)

Retraction Note: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2026)

Retraction Note: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2026)

Bacteriophage-Based Vaccine Platform for Next Generation Vaccine Development Against Bovine Tuberculosis and Other Pulmonary Diseases of Animals - Shahzar Khan; Nadia Ilyas; Fida Ullah Khan; Aneela Nawaz; Mohammed Raashid; Muhammad Ismail Khan; Momina Aamir; Aamer Ali Shah; Malik Badshah; Brekhna Alam; Samiullah Khan (International Journal of Peptide Research and Therapeutics, 2026)

Efficacy and safety of lorundrostat in uncontrolled hypertension: A GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Shree Rath; Javeria Javed; Akif Shahid Khan; Abdul Moiz; Muhammad Ansab; Alishba Hameed; Zaryab Bacha; Zarar Ahmad Khan Afridi; Khushal Khan; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Bukiniczia cabulica (Boiss.) Lincz. ameliorate diabetes-induced neuropathy: analgesic, anti-diabetic and anti-neuropathic using enzyme inhibitory, molecular docking and in-vivo studies - Zeeshan Ahmad; Mushtaq Ahmad Mir; Muhammad Shahid; Nasreena Bashir; Alam Zeb; Mehreen Ghufran; Falak Naz; Muhammad Ayaz (Inflammopharmacology, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Harnessing Indonesian Seaweed Biodiversity: A Comprehensive Two‐Decade Review of Cultivation, Bioactive Compounds, and Applications - Kasmiati Kasmiati; Ade Wahyul Fajri Alimin; Fatchurrachman Fatchurrachman; Jamaluddin Fitrah Alam; Syahrul Syahrul; Aswin Aswin; Fahrurrozi Fahrurrozi; Dedy Muhammad Iqbal; Mella Sarah Elmania (New Zealand Journal of Marine and Freshwater Research, 2026)
Indonesia is home to a high diversity of seaweeds, encompassing both wild and cultivated species. Over the past two decades, seaweed aquaculture production has increased 23‐fold, primarily driven by the eastern regions of the archipelago. This review systematically synthesizes two decades of research and development efforts, focusing on cultivation practices, the diversity of bioactive compounds isolated from Indonesian seaweeds, and their broad applications. It also evaluates literature and production data, highlighting the remarkable potential of Indonesian seaweeds as sources of bioactive components such as peptides, pigments, polyphenols, and polysaccharides, offering various health benefits, including antioxidant, anti‐inflammatory, anticancer, and antiviral properties. Furthermore, the review explores the potential use of seaweed across sectors, including animal feed, agriculture, cosmetics, and food, while specifically addressing the dynamics of carrageenan production in Indonesia‐currently the world's largest producer of carrageenan seaweed. Nonetheless, several challenges remain, particularly regarding sustainable farming practices, efficient bioprospecting, value chain development, and scalability of industrial applications. Addressing these issues is essential to ensure the long‐term viability and competitiveness of Indonesia's seaweed industry. This review underscores the strategic importance of integrating biodiversity utilization with biotechnological and industrial innovation to unlock the full socioeconomic and environmental potential of Indonesia's seaweed resources.

Greenhouse gas emission modeling for gulf cooperation council countries with boosting techniques - Muhammad Muhitur Rahman; Md Shafiul Alam; Bijoy Mitra; Mohammad Shahedur Rahman; Aftab Ahmad Khan; Muhammad Tahir Amin; Abdulmoez Al Ismaeel; Syed Masiur Rahman (Environment, Development and Sustainability, 2026)

Radiation hazards from 226 Ra, 232 Th and 40 K content in drinking waters of Islamabad, Pakistan - Junaid Ahmed; Dimitrios Nikolopoulos; Aftab Alam; Muhammad Ali Shah; Waqar Ali Zafar; Georgios Priniotakis (Isotopes in Environmental and Health Studies, 2026)

Enhancing Lodging Resistance in Rapeseed Strategies for Sustainable Agriculture and Yield Improvement - Shahid Ullah Khan; Umer Mahmood; Muhammad Sirab Khan; Minchao Qian; Shengting Li; Osama Alam; Yonghai Fan; Hui Wang; Wei Chang; Hameed Gul; Shah Fahad; Kun Lu (Journal of Plant Growth Regulation, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Eco-Friendly Gum Arabic–Essential Oil Coatings for Decay Control and Quality Preservation of Pomegranate Fruit During Storage - Muhammad Waqar Alam; Sumreen Anjum; Mubeen Sarwar; Adnan Mukhtar; Akhtar Hameed; Tanveer Hussain; Tauhid Iqbal (Applied Fruit Science, 2026)

Intravenous thrombolysis as an adjunct to endovascular thrombectomy in acute basilar artery occlusion: a GRADE-assessed systematic review and meta-analysis - Shree Rath; Umama Alam; Aamna Kashif; Muhammad Ansab; Hafiza Tooba Siddiqui; Muhammad Burhan; Zarar Ahmad Khan Afridi; Ahmad Khan; Aiman Gulalay; Bilal Aslam; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Influence of the South Pacific high on surface turbulent heat fluxes and its implications for summer heat extremes over eastern Australia - Nasir Ilyas; Muhammad Jawed Iqbal; Maqsood Alam (Acta Oceanologica Sinica, 2026)

Green Practices, knowledge processes and women’s business performance in Pakistan’s manufacturing sector - Said Muhammad; Yin Zhichao; Sajjad Alam; Naveed Khan (Environment, Development and Sustainability, 2025)

Genome-wide identification and transcriptome-based expression analysis of hybrid sugarcane calmodulin-binding transcription activators under drought - Vitor Luciano Costa da Silva; Ana Maria Martinez; Maqsood Alam; Muhammad Noman; Antonio Chalfun-Junior (Plant Gene, 2025)

Starvation-induced metabolic adaptations in immobilized Desertifilum tharense BERC-3 for improved nutrient recovery from swine wastewater - Muhammad Usman; Md. Asraful Alam; Kerui Su; Anqi Zhao; Muhammad Aamer Mehmood; Zhang Beixiao; Ayesha Shahid; A.E. Solovchenko; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Sustainable slope stabilization: root-induced stiffness and damping control in sandy soils under cyclic loading - Ismail Shah; Yuan-Jun Jiang; Mehtab Alam; Xia Xin; Muhammad Mudassar Rehman (CATENA, 2025)

Pediococcus pentosaceus PP34 Ameliorates 5-Fluorouracil-Induced Intestinal Mucositis via Inhibiting Oxidative Stress and Restoring the Gut Microbiota - Yuanyuan He; Feiran Li; Yu Zhang; Xiaohui Zhu; Zhengrong Lin; Linxiao Li; Shah Nawaz; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Jiakui Li (Probiotics and Antimicrobial Proteins, 2025)

Comparative analysis of rooting abilities between cuttings of trifoliate orange and Micro-Tom tomato: hormonal and molecular insights into adventitious root formation - Abebe Assefa Gobena; Abdelmonem Elshahat; Hai-Qiang Liu; Dong-Hai Liu; Han Han; Yin Luo; Shariq Mahmood Alam; Muhammad Ateeq; Muhammad Abbas Khan; Yong-Zhong Liu (Molecular Biology Reports, 2025)

Platelets and mitochondria: the calcium connection - Durre Shehwar; Saima Barki; Alessandro Aliotta; Debora Bertaggia Calderara; Lucas Veuthey; Cindy Pereira Portela; Lorenzo Alberio; Muhammad Rizwan Alam (Molecular Biology Reports, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Ozone‐Tolerant Rice for Air‐Polluted Environments - Muhammad Shahedul Alam; Mirza Mofazzal Islam; Minh Khue Do; Blessing Omo Osimahon; Aishwarya Kushal Karki; Aleena Ittapad Baburajan; Marc Hartung; Sawitree Autarmat; Yanru Feng; Matthias Wissuwa; Michael Frei (Global Change Biology, 2025)
Recent decades have witnessed a surge in tropospheric ozone concentrations across many Asian countries, including Bangladesh, posing a significant threat to rice yields and regional food security. This study presents a comprehensive marker‐assisted breeding program designed to introgress two quantitative trait loci (QTL) conferring ozone tolerance into elite Bangladeshi rice varieties. We crossed the donor landrace Kasalath with high‐yielding varieties BRRI dhan28 and Binadhan‐11, generating BC 2 F 4 lines with an average of 87% recipient parent genome recovery. These lines harbored diverse combinations of positive alleles at the target QTLs while retaining the agronomic traits of modern rice varieties. In controlled open‐top‐chamber experiments, the presence of these QTLs in elite backgrounds mitigated ozone stress symptoms, reduced physiological damage such as lipid peroxidation or loss in photosynthetic CO 2 assimilation rates, and alleviated yield losses. Field trials conducted in a high ozone stress environment in Bangladesh, with and without the ozone protectant ethylenediurea (EDU), revealed that sensitive recipient parents suffered under ambient ozone concentrations. In contrast, the ozone‐tolerant lines exhibited significantly less yield loss and were less affected by pollution. Our findings demonstrate the efficacy of marker‐assisted breeding in adapting rice to changing atmospheric conditions, offering a robust strategy for safeguarding food security in the face of global change.

Trace Metal Contamination in Marine Fish Species: Implications for Food Safety and Human Health - Md. Samrat Mohay Menul Islam; Umme Hafsa Tuhin; Md. Ashraful Islam; Lutfunnesa Tamanna; Mahbub Alam; Muhammad Abu Bakar; Md. Manzoorul Kibria; Sreebash Chandra Battacherjee; Mohammad Shamsil Arafeen (Biological Trace Element Research, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Interfacial engineering of CdMnS/gC3N4@rGO heterostructure for visible light-driven photocatalytic degradation of ciprofloxacin - Umair Alam; Qamar T. Siddiqui; Rishabh A. Omar; Mohammad Kashif; Zahid M. Bhat; Muhammad A.Z.G. Sial; Jae-Jin Shim; Mohammad Qamar; Nishith Verma (Journal of Water Process Engineering, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Wooden ash based nylon fiber reinforced concrete: experimental study on concrete strength properties - Muhammad Sheraz; Qiang Yuan; Muhammad Alam; Muhammad Faisal Javed (Innovative Infrastructure Solutions, 2025)

Environmental Concern and Digital Engagement as Drivers of Circular Product Buying Intention in Malaysia: an Integrated S-O-R, TPB, and DOI Perspective - Husam Ahmad Kokash; Mst. Nilufar Ahsan; Muhammad Haroon Hafeez; Amira Naqeeb Khattak; Saif Ahmed; Syed Shah Alam (Circular Economy and Sustainability, 2025)

How likely are high schools to adopt vegetable gardens to combat food insecurity? - Ayesha Noor Fatima; Khurram Yousaf; Muhammad Waqas Alam Chattha (Environment, Development and Sustainability, 2025)

PM2.5 pollution and its correlation with meteorological parameters over the four capital cities of Pakistan - Bahadar Zeb; Jawad Nasir; Khan Alam; Allah Ditta; Muhammad Arif Aman; Muhammad Shafiq (Environmental Monitoring and Assessment, 2025)

Retraction Note: Pathways towards environmental sustainability: exploring the influence of aggregate domestic consumption spending on carbon dioxide emissions in Pakistan - Muhammad Zubair Chishti; Naushad Alam; Muntasir Murshed; Abdul Rehman; Daniel Balsalobre-Lorente (Environmental Science and Pollution Research, 2025)

Avian influenza outbreak in Cambodia: a public health concern - Muhammad Abdullah Ali; Alishba Hameed; Umama Alam; Zaryab Bacha; Ahmad Khan; Sangeen Khan (Infectious Diseases, 2025)

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Sustainable kaolin-crosslinked kappa-carrageenan hydrogel as an efficient adsorbent for cationic dye removal from wastewater - Fekri Abdulraqeb Ahmed Ali; Javed Alam; Ahmed S. Al-Fatesh; Farid Fadhillah; Badr M. Thamer; Muhammad Ali Shar; Mansour Alhoshan (Journal of Water Process Engineering, 2025)

Effects of Planting Date and Genotype on Potato Growth and Yield Determination in a Sub-Tropical Continental Growing Environment - Muhammad Sohail Khan; Gerrit Hoogenboom; Syeda Mehwish Gillani; Alam Syed Shah; Ilham Khan (Potato Research, 2025)

Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2025)

Prediction of compressive strength of stone dust-based fly ash bricks: experimental study and advanced machine learning algorithm - Mehtab Alam; Adil Khan; Muhammad Umar; Tauqir Ahmed; Ahmad Yar Mazari; Muhammad Usman Arshad (Innovative Infrastructure Solutions, 2025)

Long-term fertilization with crop residue management enhances soil structure and the yield of sweet potato by optimizing soil organic carbon and acidity - Imtiaz AHMED; Jing HUANG; Jiwen LI; Nano A. DABA; Zhe SHEN; Kiya A. TADESSE; Mahmoud ABDELAZIZ; Md A. ALAM; Muhammad N. KHAN; Philip T. SINGBAH; Jun YAN; Huimin ZHANG (Pedosphere, 2025)

Sustainable immobilization strategy for Desertifilum tharense BERC-3 on corncobs to enhance biomass production and high-value metabolites - Muhammad Usman; Md Asraful Alam; Ayesha Shahid; Zhang Beixiao; Aqib Zafar Khan; Anqi Zhao; A.E. Solovchenko; Muhammad Aamer Mehmood; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Advancing comfort and efficiency: Radiant heating and cooling systems for sustainable architecture - Tarek Abedin; Md Mahfuzur Rahman; Zihad Hasan Joy; Khaled Alnamasi; Irfan Anjum Badruddin; Muhammad Nasir Bashir; Mohammad Nur-E-Alam (Building and Environment, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Correction: Mathematical Modelling for Predicting Wastewater Treatment Efficiency Through Specialised Electrocoagulation - Monzur Alam Imteaz; Muhammad Atiq Ur Rehman Tariq; Zohreh Rajabi; Amimul Ahsan (International Journal of Environmental Research, 2025)

Mathematical Modelling for Predicting Wastewater Treatment Efficiency Through Specialised Electrocoagulation - Monzur Alam Imteaz; Muhammad Atiq Ur Rehman Tariq; Zohreh Rajabi; Amimul Ahsan (International Journal of Environmental Research, 2025)
Based on experimental results on different pollutants removal efficiencies through a specialized electrocoagulation system, simple mathematical models were developed for the predictions of pollutants’ removal efficiencies for any combination of input conditions. Based on earlier experimental results two independent variables, flowrate and voltage were considered for the derivations of the generalized equations. Based on individual experimental results, relationships between flowrate and pollutant removal efficiency was derived using best-fit relationship for eight different pollutants; BOD, COD, Ammonia, TSS, TDS, Chloride, Turbidity and Hardness. Then individual relationships for different voltages were amalgamated to a single equation, which is capable to predict the specific pollutant removal efficiency for any flowrate under any voltage. Except Ammonia and TSS, developed models’ predicted results are having excellent match with the measured pollutants’ removal efficiencies having correlation coefficients (R 2 ) between modeled and measured values ranging from 0.99 to 1.0. Correlation coefficient values for Ammonia and TSS were 0.96 and 0.94 respectively. Other standard error statistics were also low; RMSE ranging from 0.21 to 3.54, MAE ranging from 0.17 to 2.33 and RAE ranging from 0.0 to 0.08. Among all the developed models, highest performing model was for the BOD having an R 2 value of 1.0 and RAE value of 0.0.

Asteraceae in Pakistan and Kashmir with special emphasis on distribution pattern and endemism - Muhammad Qaiser; Anjum Perveen; Jan Alam; Haidar Ali; Roohi Abid (Genetic Resources and Crop Evolution, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Integrating machine learning and discrete choice modeling for enhanced shopping destination choice model - MD Jahedul Alam; Niaz Mahmud; Muhammad Ahsanul Habib (Travel Behaviour and Society, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

Advancements in the production methods and recycling of multilayer plastics with sustainable applications: A comprehensive review - Maha Awjan Alreshidi; Krishna Kumar Yadav; G. Shoba; Amel Gacem; S. Padmanabhan; T. Vinod Kumar; Ahmed M. Fallatah; Javed Khan Bhutto; Fahad M. Aldosari; Manawwer Alam; Muhammad A. Abo El-Khair; P. Tamizhdurai; et al. (Chemical Engineering Journal, 2025)

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Spatiotemporal dynamics of water and sediment characteristics in Kaptai Lake: implications for sustainable management - Saifuddin Rana; Mohammad Shakil Khan; Farhan Azim; Muhammad Obaidullha; Ariful Islam Milon; Zobair Alam Sunny; Sk. Ahmad Al Nahid; Shahida Arfine Shimul (Environmental Monitoring and Assessment, 2025)

Fabrication of hydroxyapatite-based scaffold and improvement of hardness by control addition of silica - Md. Kawcher Alam; Md. Sahadat Hossain; Muhammad Shahriar Bashar; Newaz Mohammed Bahadur; Samina Ahmed (Next Research, 2025)

Patho-physiological effects of environmental relevant concentrations of lufenuron in male Japanese quails - Silwat Saeed; Gulnaz Afzal; Hafiz Muhammad Ali; Riaz Hussain; Raheela Jabeen; Shumaila Kiran; Rehana Iqbal; Sana Alam; Amna Jalal; Zaib un Nisa; Dalia Fouad; Farid Shokry Ataya; et al. (Environmental Research, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

An automatic approach for the classification of lumpy skin disease in cattle - Fakhre Alam; Asad Ullah; Mohammed A. Rohaim; Muhammad Munir; Aftab Hussain (Tropical Animal Health and Production, 2025)

Assessment of Susceptibility of Potato (Solanum tuberosum L.) Cultivars to Root Lesion Nematode, Pratylenchus penetrans, and Disease Impact on Plant Growth and Tuber Weight - Nehan Ain; Ishrat Naz; Maria; Syed Sartaj Alam; Muhammad Haris (Potato Research, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Removal of copper (II) by spinel ferrite oxides and rGO composite electrodes in capacitive deionization - Rahat Alam; Muhammad Faheem; Ahmed Alhajaj; Yao He; Linda Zou (Journal of Environmental Chemical Engineering, 2025)

Arsenic speciation in soil from urban recreational parks and human health risk assessment - Muhammad Amjad Khan; Javed Nawab; Tasneem Sarwar; Anwarzeb Khan; Iqbal Ahmad; Muhammad Waqas; Shah Nawaz Khan; Mehboob Alam; Kalsoom Kalsoom; Muhammad Ziad; Sardar Khan (Urban Ecosystems, 2025)

A novel CLRN2 variant: expanding the mutation spectrum and its critical role in isolated hearing impairment - Farooq Ahmad; Arif Mahmood; Ibrahim Abdullah Almazni; Afnan Mohammed Shakoori; Fatemah Alhakami; Qamre Alam; Muhammad Ismail; Muhammad Umair (Genes & Genomics, 2025)

Correction: Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Comprehensive analysis and human health risk assessment of tap water quality in Dhaka City, Bangladesh: Integrating source identification, index-based evaluation, and heavy metal assessment - Tasrif Nur Ariyan; Shamshad Begum Quraishi; Md. Nur E Alam; Muhammad Shahidur Rahman Khan; Farzana Ferdous Faria; Alamgir Kabir (Journal of Hazardous Materials, 2025)

Chitosan Induced Modification in Morpho-Physiological, Biochemical and Yield Attributes of Pea (Pisum Sativum L.) Under Salt Stress - Sumreen Anjum; Qurat-ul Ain; Mubeen Sarwar; Muhammad Waqar Alam; Zain Mushtaq; Adnan Mukhtar; M. Irfan Ashraf; Abdulrahman Alasmari (Journal of Soil Science and Plant Nutrition, 2025)

Sensory chemistry of Spirulina: Unveiling trends and innovations in aromatic volatile organic compound biosynthesis in off-flavors and odor mitigation strategies - Ayesha Shahid; Zihao Fan; Kerui Su; Anqi Zhao; Muhammad Aamer Mehmood; Jo-Shu Chang; A.E. Solovchenko; Md Asraful Alam; Jingliang Xu (Trends in Food Science & Technology, 2025)

Retraction notice to “A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites” [Fuel 336 (2023) 126930] - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Management of the lignocellulosic structure of agricultural straw and improving energy productivity - Altaf Alam Noonari; Muhammad Safar Korai; Munawar Ali Pinjaro; Ghulam Shabir Solangi; Arthur J. Ragauskas (Environment, Development and Sustainability, 2024)

PPG2RespNet: a deep learning model for respirational signal synthesis and monitoring from photoplethysmography (PPG) signal - Md Nazmul Islam Shuzan; Moajjem Hossain Chowdhury; Saadia Binte Alam; Mamun Bin Ibne Reaz; Muhammad Salman Khan; M. Murugappan; Muhammad E. H. Chowdhury (Physical and Engineering Sciences in Medicine, 2024)

Inhibition of mitochondrial calcium transporters alters adp-induced platelet responses - Durre Shehwar; Saima Barki; Alessandro Aliotta; Lucas Veuthey; Debora Bertaggia Calderara; Lorenzo Alberio; Muhammad Rizwan Alam (Molecular Biology Reports, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

Investigations of aerosol types classification and PM2.5 concentrations: A case study of two major cities in Pakistan - Muhammad Zeeshan; Khan Alam (Air Quality, Atmosphere & Health, 2024)

Knockdown of the glucosamine-6-phosphate N-acetyltransferase gene by RNA interference enhances the virulence of entomopathogenic fungi against rice leaffolder Cnaphalocrocis medinalis - Muhammad Shakeel; Ashraf Khan; Juan Du; Abdul Basit; Guangming Yang; Khalid Haddi; Sohail Abbas; Aleena Alam; Shangwei Li (Pesticide Biochemistry and Physiology, 2024)

Monitoring groundwater vulnerability for sustainable water resource management: A DRASTIC-based comparative assessment in a newly township area of Bangladesh - Muhammad Anwar Iqbal; Mohammed Abdus Salam; Md Nur-E-Alam; Nusrat Jahan Rubaida; Hafizur Rahman; Mohammed Faruque Uddin (Groundwater for Sustainable Development, 2024)

Site Response Analysis Considering Site-Affects Leading to Seismic Microzonation Map of Lahore - Maham Basharat; Ajwat Mustafa; Muhammad Umar; Mehtab Alam; Umair Ali; Muhammad Irfan (Geotechnical and Geological Engineering, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Ensemble transfer learning using MaizeSet: A dataset for weed and maize crop recognition at different growth stages - Zeynep Dilan Daşkın; Muhammad Shahab Alam; Muhammad Umer Khan (Crop Protection, 2024)

Emerging therapeutic avenues against Cryptosporidium: A comprehensive review - Munwar Ali; Chang Xu; Jia Wang; Muhammad Fakhar-e-Alam Kulyar; Kun Li (Veterinary Parasitology, 2024)

Agricultural productivity and rural poverty in China: The impact of land reforms - Irfan Ullah; Vishal Dagar; Tauhidul Islam Tanin; Alam Rehman; Muhammad Zeeshan (Journal of Cleaner Production, 2024)

An efficient zero-labeling segmentation approach for pest monitoring on smartphone-based images - L. Minh Dang; Sufyan Danish; Asma Khan; Nur Alam; Muhammad Fayaz; Dinh Khuong Nguyen; Hyoung-Kyu Song; Hyeonjoon Moon (European Journal of Agronomy, 2024)

Design anticancer potential of Zn(II)isoleucinedithiocarbamate complex on MCF-7 cell lines: synthesis, characterization, molecular docking, molecular dynamic, ADMET, and in-vitro studies - Rizal Irfandi; Indah Raya; Ahyar Ahmad; Ahmad Fudholi; Riswandi; Santi Santi; Wynda Puspa Azalea; Suriati Eka Putri; Muhammad Nur Alam; Unang Supratman; Samuel Olawale Olubode; Eid A. Abdalrazaq; et al. (Molecular Diversity, 2024)

Assessing Trace Metal-Based Human Health Risks for Commonly Used Body Soaps in Bangladesh - Ashraful Hoque; Taznova Anwar Tanbi; Nakshi Saha; Sabbir Howlader; Nobonita Sarker; Aminul Islam Chowdhury; Amitava Bandyopadhyay; Shahidul Islam; Muhammad Abu Bakar; Nur E. Alam; Ashok Kumar Chakraborty; Sumon Ganguli (Biological Trace Element Research, 2024)

Remediation of benzo[α]pyrene contaminated soil using iron naturally bearing in tropical soil: A new frontier in catalyst-free in soil remediation - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Chemosphere, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Nature exposure and mental health during the COVID-19 pandemic: A Navigation Guide systematic review with meta-analysis - Muhammad Mainuddin Patwary; Mondira Bardhan; Asma Safia Disha; Angel M. Dzhambov; Colby Parkinson; Matthew H.E.M. Browning; S.M. Labib; Lincoln R. Larson; Md. Zahidul Haque; Md Atiqur Rahman; Md Ashraful Alam; Md. Faysal Tareq; et al. (Environmental Pollution, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Predicting Standard Penetration Test N-value from Cone Penetration Test Data Using Gene Expression Programming - Mehtab Alam; Jianfeng Chen; Muhammad Umar; Faheem Ullah; Muhammad Shahkar (Geotechnical and Geological Engineering, 2024)

Vermi-remediation impacts on growth and metals bioaccumulation in tomato irrigated with wastewater - Mehboob Alam; Anwarzeb Khan; Rasheeqa Zaman; Shahnawaz Khan; Muhammad Amjad Khan; Imran Ahmad; Abdullah Jalal; Ki In Kim (Chemosphere, 2024)

A novel integrated approach employing Desertifilum tharense BERC-3 for efficient wastewater valorization and recycling for developing peri-urban algae farming system - Muhammad Usman; Aqib Zafar Khan; Sana Malik; Wenlong Xiong; Yongkun Lv; Shen Zhang; Anqi Zhao; A.E. Solovchenko; Md Asraful Alam; Abdulrahman H. Alessa; Muhammad Aamer Mehmood; Jingliang Xu (Chemosphere, 2024)

A deep learning-based theoretical protocol to identify potentially isoform-selective PI3Kα inhibitors - Muhammad Shafiq; Zaid Anis Sherwani; Mamona Mushtaq; Mohammad Nur-e-Alam; Aftab Ahmad; Zaheer Ul-Haq (Molecular Diversity, 2024)

Identification of Four Novel Candidate Genes for Non-syndromic Intellectual Disability in Pakistani Families - Iftikhar Ahmed; Muhammad Muzammal; Muzammil Ahmad Khan; Hafiz Ullah; Arshad Farid; Muhammad Yasin; Jabbar Khan; Khurshid Alam; Asif Mir (Biochemical Genetics, 2024)

The autophagy-mediated mechanism via TSC1/mTOR signaling pathway in thiram-induced tibial dyschondroplasia of broilers - Chuxian Quan; Shimeng Zhou; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Saisai Gong; Shah Nawaz; Ahmed Ezzat Ahmed; Quan Mo; Jiakui Li (Science of The Total Environment, 2024)

Spatial distribution of heavy metal abundance at distance gradients of roadside agricultural soil from the busiest highway in Bangladesh: A multi-index integration approach - Md. Saydul Islam; Md. Nur-E-Alam; Muhammad Anwar Iqbal; Md. Badiuzzaman Khan; Shamim Al Mamun; Md. Yunus Miah; Md. Rasheduzzaman; S. Appalasamy; Mohammed Abdus Salam (Environmental Research, 2024)

Impact of extreme weather events on mental health in South and Southeast Asia: A two decades of systematic review of observational studies - Muhammad Mainuddin Patwary; Mondira Bardhan; Md Atiqul Haque; Syed Moniruzzaman; Johanna Gustavsson; Md Maruf Haque Khan; Jenni Koivisto; Marium Salwa; Saidur Rahman Mashreky; A.K.M. Fazlur Rahman; Anika Tasnim; Md Redwanul Islam; et al. (Environmental Research, 2024)

Electrochemical C-C coupling mediated by novel Sn-SnO2 supported Cu single atoms: The case of CO2 conversion to ethanol - Muhammad Aurang Zeb Gul Sial; Na Guo; Abdul Jalil; Muhammad Abbas; Muhammad Mateen; Sami Ullah; Umair Alam; Zahid Manzoor Bhat; Arshad Hussain; Xingke Cai; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Microbiota and soil fauna mediate litter decomposition and associated carbon and nitrogen dynamics in mangrove blue carbon ecosystems: insights from a coastal lagoon in Malaysia - Mohammad Ahsanul Islam; Md Masum Billah; Mohd Hanafi Idris; Wan Mohd Rauhan Wan Hussin; Md Khurshid Alam Bhuiyan; Muhammad Shariefuddin Bin Mohd Sukeri; Abu Hena Mustafa Kamal (Hydrobiologia, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Unraveling the Endocannabinoid System: Exploring Its Therapeutic Potential in Autism Spectrum Disorder - Ankit Jana; Arnab Nath; Palash Sen; Swikriti Kundu; Badrah S. Alghamdi; Turki S. Abujamel; Muhammad Saboor; Chan Woon-Khiong; Athanasios Alexiou; Marios Papadakis; Mohammad Zubair Alam; Ghulam Md Ashraf (NeuroMolecular Medicine, 2024)
The salient features of autism spectrum disorder (ASD) encompass persistent difficulties in social communication, as well as the presence of restricted and repetitive facets of behavior, hobbies, or pursuits, which are often accompanied with cognitive limitations. Over the past few decades, a sizable number of studies have been conducted to enhance our understanding of the pathophysiology of ASD. Preclinical rat models have proven to be extremely valuable in simulating and analyzing the roles of a wide range of established environmental and genetic factors. Recent research has also demonstrated the significant involvement of the endocannabinoid system (ECS) in the pathogenesis of several neuropsychiatric diseases, including ASD. In fact, the ECS has the potential to regulate a multitude of metabolic and cellular pathways associated with autism, including the immune system. Moreover, the ECS has emerged as a promising target for intervention with high predictive validity. Particularly noteworthy are resent preclinical studies in rodents, which describe the onset of ASD-like symptoms after various genetic or pharmacological interventions targeting the ECS, providing encouraging evidence for further exploration in this area.

In-depth characterization of particulate matter in a highly polluted urban environment at the foothills of Himalaya–Karakorum Region - Bahadar Zeb; Khan Alam; Zhongwei Huang; Fatma Öztürk; Peng Wang; Lyudmila Mihaylova; Muhammad Fahim Khokhar; Said Munir (Environmental Science and Pollution Research, 2024)

Advanced oxidation of polycyclic aromatic hydrocarbons in tropical soil: Self-catalytic utilization of natural iron contents in an oxygenation reactor supported with persulfate - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Science of The Total Environment, 2024)

Impact of green space and built environment on metabolic syndrome: A systematic review with meta-analysis - Muhammad Mainuddin Patwary; Mohammad Javad Zare Sakhvidi; Sadia Ashraf; Payam Dadvand; Matthew H.E.M. Browning; Md Ashraful Alam; Michelle L. Bell; Peter James; Thomas Astell-Burt (Science of The Total Environment, 2024)

New bisbenzylisoquinoline alkaloid, isolation and structure elucidation from Cocculus pendulus - Shaikh Ziauddin Sultani; Muhammad Aijaz Anwar; Muhammad Shahab Alam (Natural Product Research, 2024)

A Systematic Review of Crop Planning Optimisation Under Climate Change - Marcus Randall; Karin Schiller; Andrew Lewis; James Montgomery; Muhammad Shahinur Alam (Water Resources Management, 2024)
Optimising the use of natural resources for food production in the context of changing climate is an increasingly important issue. Optimisation techniques have been shown to be remarkably effective for planning problems, and tools regional planners and farmers can use to determine the viability of agricultural land use planning into the future. This paper systematically reviews the recent literature in this area and draws out the key emerging themes: few studies to date have explicitly incorporated climate projections into optimisation models; increased tension for water resources between stakeholders; and various agricultural production systems of complex versions of crop planning. From this review it can be seen that increasing concentration on the use of climate projection models within agriculturally-oriented optimisation processes is a necessity.

Exercise Improves Cerebral Blood Flow and Functional Outcomes in an Experimental Mouse Model of Vascular Cognitive Impairment and Dementia (VCID) - Mohammad Badruzzaman Khan; Haroon Alam; Shahneela Siddiqui; Muhammad Fasih Shaikh; Abhinav Sharma; Amna Rehman; Babak Baban; Ali S. Arbab; David C. Hess (Translational Stroke Research, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

Assessing the climate vulnerability of mountain agriculture: a case study of Haramosh Valley in Central Karakoram, Pakistan - Muneer Alam; Muhammad Zafar Khan; Farida Begum; Tasawar R. Baig (Environment, Development and Sustainability, 2024)

Potential application of 2D nano-layered MXene in analysing and remediating endocrine disruptor compounds and heavy metals in water - Muhammad Nur’ Hafiz Rozaini; Kuan Shiong Khoo; Muhammad Amirul Aizat Mohd Abdah; Baranitharan Ethiraj; Mohammad Mahtab Alam; Aliya Fathima Anwar; Normawati M. Yunus; Chin Seng Liew; Jun Wei Lim; Chii-Dong Ho; Woei-Yenn Tong (Environmental Geochemistry and Health, 2024)

Wastewater-Grown Algal Biomass as Carbon-neutral, Renewable, and Low Water Footprint Feedstock for Clean Energy and Bioplastics - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Nabeel Haider; Sana Malik; Hafiza Aroosa Malik; Md. Asraful Alam; Jingliang Xu; Abdulrahman H. Alessa; Aqib Zafar Khan; Raj Boopathy (Current Pollution Reports, 2024)

Evaluating the roles of energy innovation, fossil fuel costs and environmental compliance towards energy transition in advanced industrial economies - Muhammad Farhan Bashir; Muhammad Shahbaz; Beiling Ma; Khorshed Alam (Journal of Environmental Management, 2024)

Probiotic Potential of Bacillus amyloliquefaciens Isolated from Tibetan Yaks - Yuanyuan He; Feiran Li; Wenqian Zhang; Miao An; Aoyun Li; Yaping Wang; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Jiakui Li (Probiotics and Antimicrobial Proteins, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

Soil Application of Potassium Maintains Growth, Water Relations, Yield and Seed Quality of Quinoa in Salt Affected Soils - Mehmood Ejaz; Muhammad Amir Bakhtavar; Shahid Iqbal; Mahmood Alam Khan; Raheela Jabeen; Nazish Jabeen; Ali Raza (Journal of Crop Health, 2024)

WITHDRAWN: Valorization of Algal Biomass to Synthesize Heterogeneous gCN-Biochar Photocatalyst for the Treatment of Industrial Wastewater using Photocatalysis-Persulfate Oxidation Process - Aqsa Shafique; Hafiz Muhammad Uzair Ayub; Javed Iqbal; Shanawar Hamid; Fawad Ashraf; Muhammad Saif Ur Rehman; S. Boukhari; Mohamed A. Habila; Alam Nawaz; Tahir Fazal (Chemosphere, 2024)

Remote sensing and GIS based multi-criteria analysis approach with application of AHP and FAHP for structures suitability of rainwater harvesting structures in Lai Nullah, Rawalpindi, Pakistan - Rashid Ahmad; Hamza Farooq Gabriel; Farooq Alam; Riaz Zarin; Abdur Raziq; Muhammad Nouman; Hsu-Wen Vincent Young; Yuei-An Liou (Urban Climate, 2024)

Alteration of carbon and nitrogen allocation in winter wheat under elevated ozone - Yanru Feng; Muhammad Shahedul Alam; Feng Yan; Michael Frei (Plant Science, 2024)

The path of microplastics through the rare biodiversity estuary region of the northern Bay of Bengal - Al-Nure Mubin; Abu Reza Md. Towfiqul Islam; Mehedi Hasan; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Sha Alam; Md. Refat Jahan Rakib; Muhammad Saiful Islam; Nasima Momtaz; Venkatramanan Senapathi; Abubakr M. Idris; et al. (Journal of Contaminant Hydrology, 2024)

Evaluation of occupational health and safety intervention for the waste and sanitation workers in Bangladesh during COVID-19 - Dewan Muhammad Shoaib; Tanvir Ahmed; Kazy Farhat Tabassum; Mehedi Hasan; Fazle Sharior; Mahbubur Rahman; Makfie Farah; Md Azizur Rahman; Alauddin Ahmed; James B. Tidwell; Mahbub-Ul Alam (International Journal of Hygiene and Environmental Health, 2024)

Genetic variability for the leaf rust resistance and its association with morphological yield contributing traits in bread wheat germplasm under field condition - Muhammad Farooq Naseer; Mueen Alam Khan (Australasian Plant Pathology, 2024)

Enhancing coastal ecosystem resilience: Investigating the interplay between safety criteria and ferry employee's perceptions to address climate change impacts - Muhammad Azizol Azmi; Kasypi Mokhtar; Noor Apandi Osnin; Suzanna Razali Chan; Gadah Albasher; Atif Ali; Alam Nawaz; Olakunle Oloruntobi; Lai Fatt Chuah (Environmental Research, 2023)

Appraisal of anti-arthritic potential of Coronopus didymus (L.) Sm. aqueous extract and its safety study in Wistar rats - Ammara Saleem; Huma Khalid; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2023)

Comparative Analysis of IgG Antibody Titers Induced by Three Different SARS-COV-2 Vaccines in Healthy Adults of Pakistan - Nayab Batool Rizvi; Hassam Farooq; Qaiser Alam Khan; Muhammad Zeeshan Rana; Sehrish Zaffar; Muhammad Shahid; Nazim Hussain (Current Microbiology, 2023)

Policies and regulations for solar photovoltaic end-of-life waste management: Insights from China and the USA - Amjad Ali; Sheraz Alam Malik; Md Shafiullah; Muhammad Zeeshan Malik; Md Hasan Zahir (Chemosphere, 2023)

Graphene-grafted bimetallic MOF membranes for hazardous & toxic contaminants treatment - Ayesha Rehman; Zaib Jahan; Muhammad Bilal Khan Niazi; Tayyaba Noor; Farhan Javed; Sarah I. Othman; Mostafa R. Abukhadra; Alam Nawaz (Chemosphere, 2023)

Long-term quantification of pre and post-monsoon surface water area of Bangladesh - Syed Muhimeen Ahmed; Hasan Muhammad Abdullah; Tahsin Tanha Chowdhury; Abiar Rahman; Mohammad Zahangeer Alam (Remote Sensing Applications: Society and Environment, 2023)

Ion selective electrosorption by two pseudocapacitive intercalating nanocomposite electrodes - Rahat Alam; Muhammad Faheem; Yao He; Xiao Su; Linda Zou (Desalination, 2023)

Luminescence fingerprints fluvial sediment transport from the Tibetan Plateau to the Bangladesh Delta - Aimin Zhang; Qihui Gao; Sufi Mostafizur Rahman; Muhammad Mahbubul Alam; Yujie Guo; Yiwei Chen; Jie Cheng; Huiying Wang; Ping Wang; Jiafu Zhang; Chaolu Yi; Gang Hu (Earth and Planetary Science Letters, 2023)

Effects of long-term organic and inorganic fertilization on greenhouse gas emissions and soil nutrient stoichiometry in a rice–rice–fallow cropping system - Md Ashraful Alam; Jing Huang; Muhammad Numan Khan; Nano Alemu Daba; Lu Zhang; Zhe Shen; Jiwen Li; Lisheng Liu; Tianfu Han; Nafiu Garba Hayatu; Md Arifur Rahaman; Huimin Zhang (Agriculture, Ecosystems & Environment, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

Sustainable remediation of dye-contaminated wastewater using novel cross-linked Hex-CCP-co-PPT microspheres - Sahid Mehmood; Fazal Haq; Mehwish Kiran; Ibrahim A. Shaaban; Mohammed A. Assiri; Muhammad Haroon; Muhammad Yasin; Arshad Farid; Alam Nawaz; Majid Majeed Akbar; Zeinhom M. El-Bahy (Chemosphere, 2023)

RETRACTED ARTICLE: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2023)

Retraction Note: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2023)

Microplastic contamination from surface waters and commercially valuable fishes of Karachi Coast, Pakistan - Nazia Arshad; Muhammad Mansoor Alam; Mazliham Bin Mohd Su’ud; Sobia Imran; Tooba Siddiqui; Khadija Saleem; Adnan Bashir; Atia Batool (Regional Studies in Marine Science, 2023)

Allantoin alleviates chromium phytotoxic effects on wheat by regulating osmolyte accumulation, secondary metabolism, ROS homeostasis and nutrient acquisition - Rizwan Alam; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Shafaqat Ali (Journal of Hazardous Materials, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Improving Nitrogen Acquisition and Utilization Through Root Architecture Remodelling: Insight from Legumes - Muhammad Nadeem; Muhammad Yahya; Jingyang Tong; Liaqut Shah; Sana Ullah Khan; Ahmad Ali; Alam Sher; Najeeb Ullah; Abdul Waheed (Journal of Plant Growth Regulation, 2023)
In crop species, nutrient deficiency severely damages plant growth and developmental processes, leading to end-yield penalties. Root architecture remodelling is considered a key factor underpinning nutrient-poor soil environments. Adequate nitrogen (N) supply can play a significant role in sustaining crop productivity on nutrient-deficient soils. However, excessive application of nitrogenous fertilizer may pollute the soil and increase the production cost for the growers. To tackle this problem, crop breeders have made tremendous efforts to improve the N-use efficiency of agricultural crops. This article summarizes the recent progress in identifying QTLs/genes, regulatory pathways, and hormonal crosstalk involved in the growth and development of legumes roots system. Moreover, we have described the progress in microbe–root symbiosis via QTLs/genes regulations, which results in improved N acquisition. Understanding the molecular mechanisms that regulate the root architecture in response to N availability may help to strengthen the root system of legumes and promote environmental friendly and sustainable agriculture.

The effect of financial stress on renewable energy consumption: evidence from US data - Mohammad Dulal Miah; Muhammad Shafiullah; Md. Samsul Alam (Environment, Development and Sustainability, 2023)

An overview on human exposure, toxicity, solid-phase microextraction and adsorptive removal of perfluoroalkyl carboxylic acids (PFCAs) from water matrices - Zakariyya Uba Zango; Baranitharan Ethiraj; Fahad S. Al-Mubaddel; Mohammad Mahtab Alam; Muhammad Abubakar Lawal; Haliru Aivada Kadir; Kuan Shiong Khoo; Zaharaddeen Nasiru Garba; Fahad Usman; Muttaqa Uba Zango; Jun Wei Lim (Environmental Research, 2023)

Geospatial soil loss risk assessment using RUSLE model: a study of Panjkora River Basin, Khyber Pakhtunkhwa, Pakistan - Muhammad Jamal Nasir; Said Alam; Waqas Ahmad; Sayed M. Bateni; Javed Iqbal; Mansour Almazroui; Burhan Ahmad (Arabian Journal of Geosciences, 2023)

The influence of civilized city honorary title on the urban innovation capacity - Jiabin han; Ziyi Chen; Muhammad Zeeshan; Alam Rehman; Irfan Ullah; Suleman Sarwar (Environment, Development and Sustainability, 2023)

Biometric indices, growth pattern, and physiological status of captive-reared indigenous Yellowtail brood catfish, Pangasius pangasius (Hamilton, 1822) - Md. Arifur Rahman; Md. Rased Khan Manon; Md. Rahamat Ullah; Asraful Alam; Md. Jakiul Islam; Muhammad A. B. Siddik; Mohammed Mahbub Iqbal (Environmental Science and Pollution Research, 2023)

Selective anti-cancer activity against melanoma cells using 3- O -acetyl-β-boswellic acid-loaded 3D-Printed scaffold - Fatemeh Jamshidi-adegani; Saeid Vakilian; Sulaiman Al-Hashmi; Juhaina Al-Kindi; Najeeb Ur Rehman; Yaqeen Al-Sinani; Shokoofeh Ghaemi; Khurshid Alam; Muhammad U. Anwar; Rene Csuk; Ahmed Al-Harrasi (Natural Product Research, 2023)

Modelling the asymmetric effects of renewable and nonrenewable energy consumption and financial development on CO2 emissions in India: Empirical findings from the NARDL and Wavelet Coherence Approach - Mohammad Subhan; Muhammad Irfan; Gayas Ahmad; Waseem Alam; Mohd Nasir Zameer (Environmental Science and Pollution Research, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

Biodegradation of monocrotophos by Brucella intermedia Msd2 isolated from cotton plant - Shazmin; Siti Aqlima Ahmad; Tatheer Alam Naqvi; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

The co-application of bioslurry and compost with inorganic zinc fertilizer improved soil quality, zinc uptake, and growth of maize crop - Aqarab Husnain Gondal; Muhammad Imran Khan; Sardar Alam Cheema; Muhammad Iftikhar Hussain; Basharat Ali; Muhammad Nawaz; Muhammad Dawood; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

Correction to: Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

Hybrid pseudocapacitive sodium titanate/rGO and MXene/rGO nanocomposite electrodes in capacitive deionization - Muhammad Faheem; Rahat Alam; Yao He; Linda Zou (Desalination, 2023)

Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

Supplier transaction, TMT characteristics, and the persistence of earnings: do their relationship contribute towards sustainable performance of Chinese listed manufacturing sector firms? - Wang Minghua; Yang Tao; Muhammad Zeeshan; Alam Rehman (Environmental Science and Pollution Research, 2023)

RETRACTED: A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2023)

Calcium and L-glutamate present the opposite role in managing arsenic in barley - Fanrong Zeng; Muhammad Mudassir Nazir; Temoor Ahmed; Muhammad Noman; Shafaqat Ali; Muhammad Rizwan; Mohammad Shah Alam; Jonas Lwalaba Wa Lwalaba; Guoping Zhang (Environmental Pollution, 2023)

Thiram-induced hyperglycemia causes tibial dyschondroplasia by triggering aberrant ECM remodeling via the gut-pancreas axis in broiler chickens - Quan Mo; Muhammad Fakhar-e-Alam Kulyar; Chuxian Quan; Yanmei Ding; Yan Zhang; Lihong Zhang; Huachun Pan; Jiakui Li (Journal of Hazardous Materials, 2023)

Comparative genomics with evolutionary lineage in Streptomyces bacteria reveals high biosynthetic potentials - Khorshed Alam; Md. Mahmudul Islam; Saiful Islam; Jinfang Hao; Muhammad Nazeer Abbasi; Muhammad Hayat; Muhammad Shoaib; Youming Zhang; Aiying Li (World Journal of Microbiology and Biotechnology, 2023)

The inclusive analysis of green technology implementation impacts on employees age, job experience, and size in manufacturing firms: empirical assessment - Sajjad Alam; Jianhua Zhang; Muhammad Usman Shehzad; Fredrick Ahenkora Boamah; Bingbing Wang (Environment, Development and Sustainability, 2023)

Fusarium falciforme and F. oxysporum causing postharvest fruit rot of watermelon (Citrullus lanatus) in Malaysia: A first report - Jagaathiswary Balasubramaniam; Ka Sheng Goh; Safia Fazariah Sani; Muhammad Waqar Alam; Nor Azliza Ismail; Mark L. Gleason; Hafizi Rosli (Crop Protection, 2023)

Effects of Mirabilis jalapa L. root extract and sildenafil on paroxetine-induced sexual dysfunction in male rats and characterization of its phytoconstituents by UPLC-MS - Asad Ur Rahman; Fiaz Alam; Zia Ur Rehman; Muhammad Khan; Tawseef Ahmad (South African Journal of Botany, 2023)

Environmental microplastics exposure decreases antioxidant ability, perturbs gut microbial homeostasis and metabolism in chicken - Aoyun Li; Yingli Wang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Renhao Lai; Huaisen Zhu; Kun Li (Science of The Total Environment, 2023)

The influence of compost amendments on bioaccumulation of potentially toxic elements by pea plant cultivated in mine degraded soils - Abdulnour Ali Jazem Ghanim; Muhammad Azhar Shah; Mehboob Alam; Anwarzeb Khan; Muhammad Amjad Khan; Saifur Rahman; Mabkhoot A. Alsaiari; Mohammed Jalalah; Mohammad Kamal Asif Khan; Muhammad Irfan; Zawar Hussain (Arabian Journal of Geosciences, 2023)

Ginsenoside Rg1 regulates thiram-induced chondrocytes’ apoptosis and angiogenesis in broiler chickens - Huaisen Zhu; Muhammad Fakhar-e-Alam Kulyar; Yanmei Ding; Wangyuan Yao; Quan Mo; Jiakui Li (Environmental Science and Pollution Research, 2022)

The impact of climate variables on marine fish production: an empirical evidence from Bangladesh based on autoregressive distributed lag (ARDL) approach - Mahfuza Begum; Muhammad Mehedi Masud; Lubna Alam; Mazlin Bin Mokhtar; Ahmad Aldrie Amir (Environmental Science and Pollution Research, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Wet Vibrational Precipitator: Increasing Particulate Capture Efficiency Through Vibrational Analysis - Muhammad Ali; Anbara Lutfullaeva; Khairul Alam (Aerosol Science and Engineering, 2022)

Rep-PCR Analyses Reveal Genetic Variation of Ralstonia solanacearum Causing Wilt of Solanaceaous Vegetables in Bangladesh - Md. Mosharraf Hossain; Md. Mostafa Masud; Muhammad Iqbal Hossain; Mohammad Mahbubul Haque; Mohammad Sharif Uddin; Md. Zahangir Alam; Md. Rashidul Islam (Current Microbiology, 2022)

How do farmers cope with climate change? An analysis of alternative adaptation strategies in drought-hit areas of Khyber Pakhtunkhwa—Pakistan - Imtiaz Alam Khan; Muhammad Rafiq; Sanaullah Panezai; Shahab E. Saqib; Raza Ullah; Muhammad Atiq (Natural Hazards, 2022)

Interactive effects of tropospheric ozone and blast disease (Magnaporthe oryzae) on different rice genotypes - Muhammad Shahedul Alam; Angeline Wanjiku Maina; Yanru Feng; Lin-Bo Wu; Michael Frei (Environmental Science and Pollution Research, 2022)
Rising tropospheric ozone concentrations can cause rice yield losses and necessitate the breeding of ozone-tolerant rice varieties. However, ozone tolerance should not compromise the resistance to important biotic stresses such as the rice blast disease. Therefore, we investigated the interactive effects of ozone and rice blast disease on nine different rice varieties in an experiment testing an ozone treatment, blast inoculation, and their interaction. Plants were exposed to an ozone concentration of 100 ppb for 7 h per day or ambient air throughout the growth period. Half of the plants were simultaneously infected with rice blast inoculum. Grain yield was significantly reduced in the blast treatment (17%) and ozone treatment (37%), while the combination of both stresses did not further decrease grain yields compared to ozone alone. Similar trends occurred for physiological traits such as vegetation indices, normalized difference vegetation index (NDVI), photochemical reflectance index (PRI), Lichtenthaler index 2 (Lic2), and anthocyanin reflectance index 1 (ARI1), as well as stomatal conductance and lipid peroxidation. Ozone exposure mitigated the formation of visible blast symptoms, while blast inoculation did not significantly affect visible ozone symptoms. Although different genotypes showed contrasting responses to the two types of stresses, no systematic pattern was observed regarding synergies or trade-offs under the two types of stresses. Therefore, we conclude that despite the similarities in physiological stress responses to ozone and blast, the tolerance to these stresses does not appear to be genetically linked in rice.

Probiotic Potential of Bacillus licheniformis and Bacillus pumilus Isolated from Tibetan Yaks, China - Zhibo Zeng; Jiabin Zhang; Yan Li; Kewei Li; Saisai Gong; Feiran Li; Pengpeng Wang; Mudassar Iqbal; Muhammad Fakhar-e-Alam Kulyar; Jiakui Li (Probiotics and Antimicrobial Proteins, 2022)

Genome wide analysis of DWARF27 genes in soybean and functional characterization of GmD27c reveals eminent role of strigolactones in rhizobia interaction and nodulation in Glycine max - Naveed ur Rehman; Farhat Abbas; Muhammad Imran; Intikhab Alam; Muhammad Imran; Ihteram Ullah; Muhammad Riaz; Fahim Ullah Khan (Molecular Biology Reports, 2022)

Bacterial Redox Cycling of Manganese in Calcareous Soil Enhances the Nutrients Bioavailability to Wheat - Saba Babar; Ghulam Jilani; Adil Mihoub; Aftab Jamal; Iftikhar Ahmad; Arshad Nawaz Chaudhary; Muhammad Farhan Saeed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

RETRACTED ARTICLE: Pathways towards environmental sustainability: exploring the influence of aggregate domestic consumption spending on carbon dioxide emissions in Pakistan - Muhammad Zubair Chishti; Naushad Alam; Muntasir Murshed; Abdul Rehman; Daniel Balsalobre-Lorente (Environmental Science and Pollution Research, 2022)

Trade openness and urbanization impact on renewable and non-renewable energy consumption in China - Jiabin han; Muhammad Zeeshan; Irfan Ullah; Alam Rehman; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2022)

Recycling of ferrous slag in agriculture: Potentials and challenges - Suvendu Das; Snowie Jane Galgo; Muhammad Ashraful Alam; Jeong Gu Lee; Hyun Young Hwang; Chang Hoon Lee; Pil Joo Kim (Critical Reviews in Environmental Science and Technology, 2022)

Polystichum braunii ameliorates airway inflammation by attenuation of inflammatory and oxidative stress biomarkers, and pulmonary edema by elevation of aquaporins in ovalbumin-induced allergic asthmatic mice - Ammara Saleem; Afza Mubeen; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2022)

Microalgae binary culture for higher biomass production, nutrients recycling, and efficient harvesting: a review - Md. Asraful Alam; Chun Wan; Dang Thuan Tran; M. Mofijur; Shams Forruque Ahmed; Muhammad Aamer Mehmood; Feroz Shaik; Dai-Viet N. Vo; Jingliang Xu (Environmental Chemistry Letters, 2022)

Application of Biofloc Technology for the culture of Heteropneustes fossilis (Bloch) in Bangladesh: stocking density, floc volume, growth performance, and profitability - Md Shamsuddin; M. Belal Hossain; Moshiur Rahman; Mst. Salamun Kawla; Md. Badiul Alam Shufol; Muhammad Mamunur Rashid; Md. Asadujjaman; Md. Refat Jahan Rakib (Aquaculture International, 2022)

Repurposing of existing antibiotics for the treatment of diabetes mellitus - Muhammad Shaiful Alam; Md. Sohorab Uddin; Tahmida Shamsuddin; Maruf Rubayed; Tania Sharmin; Rasheda Akter; S. M. Zahid Hosen (In Silico Pharmacology, 2022)

Calculation of urban solar radiation based on simulation and fitting of ASHRAE model constants - Atteeq Razzak; Zaheer Uddin; Muhammad Jawed Iqbal; Khan Alam (Arabian Journal of Geosciences, 2022)

Effects of interspecific competition between Aedes aegypti and Culex quinquefasciatus on their life history traits - Daniyal Ahmad; Muhammad Waqas Sumra; Rizwan Mustafa Shah; Mehboob Alam; Sarfraz Ali Shad; Unsar Naeem-Ullah; Muhammad Binyameen (International Journal of Tropical Insect Science, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

RETRACTED ARTICLE: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

Nitrification Inhibitor and Plant Growth Regulators Improve Wheat Yield and Nitrogen Use Efficiency - Khadim Dawar; Umar Rahman; Syed Sartaj Alam; Mohammad Tariq; Aamir Khan; Shah Fahad; Rahul Datta; Subhan Danish; Shah Saud; Muhammad Noor (Journal of Plant Growth Regulation, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Correction to: Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit‑Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit-Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Chlorogenic acid inhibits apoptosis in thiram-induced tibial dyschondroplasia via intrinsic pathway - Jialu Zhang; Bihao Luo; Juanjuan Liu; Muhammad Waqas; Muhammad Fakhar-e-Alam Kulyar; Kangkang Guo; Jiakui Li (Environmental Science and Pollution Research, 2021)

Correction to: Exploring determinants of financial system and environmental quality in high-income developed countries of the world: the demonstration of robust penal data estimation techniques - Muhammad Zeeshan; Jiabin Han; Alam Rehman; Irfan Ullah; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2021)

Exploring determinants of financial system and environmental quality in high-income developed countries of the world: the demonstration of robust penal data estimation techniques - Muhammad Zeeshan; Jiabin Han; Alam Rehman; Irfan Ullah; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2021)

Metabolic responses of Chinese perch (Siniperca chuatsi) to different levels of dietary carbohydrate - Yanpeng Zhang; Xu-fang Liang; Shan He; Jie Wang; Ling Li; Zhen Zhang; Jiao Li; Xu Chen; Lu Li; Muhammad Shoaib Alam (Fish Physiology and Biochemistry, 2021)

Correction to: Lineament mapping for a part of the central Sulaiman fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)

Silver nanoparticles biosynthesized from secondary metabolite producing marine actinobacteria and evaluation of their biomedical potential - Ashia Alam; Faouzia Tanveer; Ali Talha Khalil; Tanzeel Zohra; Saleh Khamlich; Muhammad Masroor Alam; Muhammad Salman; Muhammad Ali; Aamer Ikram; Zabta Khan Shinwari; Malik Maaza (Antonie van Leeuwenhoek, 2021)

Fluctuation Dynamics of Radon in Groundwater Prior to the Gansu Earthquake, China (22 July 2013: Ms = 6.6): Investigation with DFA and MFDFA Methods - Aftab Alam; Nanping Wang; Ermioni Petraki; Adnan Barkat; Fuqiong Huang; Muhammad Ali Shah; Demetrios Cantzos; Georgios Priniotakis; Panayiotis H. Yannakopoulos; Michail Papoutsidakis; Dimitrios Nikolopoulos (Pure and Applied Geophysics, 2021)

Adoption of green banking practices and environmental performance in Pakistan: a demonstration of structural equation modelling - Alam Rehman; Irfan Ullah; Fakhr-e-Alam Afridi; Zain Ullah; Muhammad Zeeshan; Arif Hussain; Haseeb Ur Rahman (Environment, Development and Sustainability, 2021)

Adaptation of AMPK-mTOR-signal pathways and lipid metabolism in response to low- and high-level rapeseed meal diet in Chinese perch (Siniperca chuatsi) - Jiao Li; Xu-Fang Liang; Muhammad Shoaib Alam; Haocan Luo; Yanpeng Zhang; Binbin Peng; Qianqian Xiao; Zhilu Zhang; Liwei Liu; Shan He (Journal of Comparative Physiology B, 2021)

Phytochemical and spectral analysis of the methanolic extracts of leaves of Murraya koenigii of Jazan, Saudi Arabia - Sivakumar Sivagurunthan Moni; Muhammad Hadi Sultan; Hafiz A. Makeen; Aamena Jabeen; Syeda Sanobar; Rahimullah Siddiqui; Zia ur Rehman; Md Shamsher Alam; Sarfaraz Ahmad; Mohamed Eltaib Elmobark; Remesh Moochikkal (Natural Product Research, 2021)

Mass evacuation microsimulation modeling considering traffic disruptions - MD Jahedul Alam; Muhammad Ahsanul Habib (Natural Hazards, 2021)

First report of Lasiodiplodia pseudotheobromae causing twig and stem blight of Gossypium hirsutum in Pakistan - Sumera Naz; Saira Mehboob; Muhammad Waqar Alam; Abdul Rehman; Muhammad Idrees (Journal of Plant Pathology, 2021)

Switching behaviors toward green brands: evidence from emerging economy - Syed Hasnain Alam Kazmi; Muhammad Saeed Shahbaz; Muhammad Shujaat Mubarik; Junaid Ahmed (Environment, Development and Sustainability, 2021)

Statistical analysis and temporal trend of annual maximum temperature with teleconnection patterns of different stations in Pakistan - Tasir Khan; Yejuan Wang; Naiming Yuan; Abdullah; Muhammad Salam; Fakhri Alam; Qasim Shah (Arabian Journal of Geosciences, 2021)

Lineament mapping for a part of the Central Sulaiman Fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)
This study aims to analyze the lineaments using the field data and a remote sensing approach, to describe their relationship with the folds, faults, and regional tectonic stress of the central Sulaiman Fold-Thrust Belt. Joint data, from nine anticlines, has been collected using the scanline method and classified into three sets (JS1, JS2, and JS3) based on their geometrical relationships. Lineaments extracted from the 30 m digital elevation model have been classified subsequently into three lineament sets (LS1, LS2, and LS3) based on the azimuths from the corresponding joint sets. A very high correlation coefficient (rs = 0.97), between the azimuths of the field joints and the remotely sensed lineaments, has been observed which validates that the lineaments are the regional representation of the local field joints. The geometrical relationship of the lineament sets with the fold hinges indicates that the older LS1 and LS2 are strongly related to the regional folding episode, while the younger LS3 is a result of local shears. The chronological interpretation of the deformational events responsible for the lineament sets is constrained by the presence of the Kingri Fault, which induces a strike-slip component within the study area. Furthermore, the controls on the joint and lineament sets, established using multivariate statistics to decipher the effects of lithological and structural contrasts on the lineament density, reveal that an increase in the lineament density can be attributed to the competence and thickness of the rock units as well as the variable local stresses across the different folds. Based on the orientations of these lineament sets, the cumulative direction of the compressive event in the NW-SE direction (310–320) coincides with the regional stress direction of the SFTB.

Silicon attenuates the negative effects of chromium stress in tomato plants by modifying antioxidant enzyme activities, ascorbate–glutathione cycle and glyoxalase system - Pravej Alam; Thamer H. Balawi; Fahad H. Altalayan; Ashraf Atef Hatamleh; Muhammad Ashraf; Parvaiz Ahmad (Acta Physiologiae Plantarum, 2021)

High density cotton population in late sowing improves productivity and tolerance to cotton leaf curl virus under semi-arid subtropical conditions - Muhammad Iqbal; Mueen Alam Khan; Sami Ul-Allah (Journal of Plant Diseases and Protection, 2021)

Correction to: First report of leaf spot caused by Albifimbria verrucaria on spinach in Pakistan - Abdul Rehman; Saira Mehboob; Muhammad Waqar Alam; Sumera Naz (Journal of Plant Pathology, 2021)

First report of leaf spot caused by Albifimbria verrucaria on spinach in Pakistan - Abdul Rehman; Saira Mehboob; Muhammad Waqar Alam; Sumera Naz (Journal of Plant Pathology, 2021)

First report of potato wilt caused by Plectosphaerella cucumerina in Pakistan - Muhammad Waqar Alam; Arif Malik; Abdul Rehman; Mubeen Sarwar; Saira Mehboob (Journal of Plant Pathology, 2021)

First report of white mould of potato caused by Sclerotinia sclerotiorum in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Arif Malik; Saira Mehboob; Mubeen Sarwar; Sher Muhammad (Journal of Plant Pathology, 2021)

Assessment of health risks and individuals’ willingness to participate in drinking water management at flood-prone Pahang River Basin, Malaysia - Lubna Alam; Labonnah Farzana Rahman; Minhaz Farid Ahmed; Md. Azizul Bari; Muhammad Mehedi Masud; Mazlin Bin Mokhtar (Environmental Geochemistry and Health, 2021)

Arbuscular mycorrhizal fungi and its major role in plant growth, zinc nutrition, phosphorous regulation and phytoremediation - Parashuram Bhantana; Muhammad Shoaib Rana; Xue-cheng Sun; Mohamed G. Moussa; Muhammad Hamzah Saleem; Muhamad Syaifudin; Ashrafuzzaman Shah; Amrit Poudel; Amar Bahadur Pun; Mufid Alam Bhat; Dhanik Lal Mandal; Sujit Shah; et al. (Symbiosis, 2021)

Solvent extraction, spectral analysis and antibacterial activity of the bioactive crystals of Sargassum aquifolium (Turner) C.Agardh from Red Sea - Sivakumar Sivagurunathan Moni; Mohammad Firoz Alam; Hafiz A. Makeen; Hassan A. Alhazmi; Muhammad Sultan; Rahimullah Siddiqui; Aamena Jabeen; Syeda Sanobar; Md Shamsher Alam; Zia Ur Rehman; Mohamed Eltyep Elmobark; Osama Madkhali; et al. (Natural Product Research, 2021)

The Surface Urban Heat Island Intensity and Urban Expansion: A comparative analysis for the coastal areas of Pakistan - Shahnilla Haider Rizvi; Hira Fatima; Khan Alam; Muhammad Jawed Iqbal (Environment, Development and Sustainability, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Landslide inventory and susceptibility assessment using multiple statistical approaches along the Karakoram highway, northern Pakistan - Mian Luqman Hussain; Muhammad Shafique; Alam Sher Bacha; Xiao-qing Chen; Hua-yong Chen (Journal of Mountain Science, 2021)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)

The role of sense of place, risk perception, and level of disaster preparedness in disaster vulnerable mountainous areas of Gilgit-Baltistan, Pakistan - Garee Khan; Javed Akhter Qureshi; Anwar Khan; Attaullah Shah; Sajid Ali; Iram Bano; Muhammad Alam (Environmental Science and Pollution Research, 2020)

Efficacy of electrolyzed water against bacteria on fresh fish for increasing the shelf-life during transportation and distribution - Alam A. K. M. Nowsad; Nakib Dad Khan; Muhammad Mehedi Hasan; Syed Md Ehsanur Rahman; Toshiyoshi Araki; Takao Yoshimatsu (Journal of Consumer Protection and Food Safety, 2020)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Activin A affects feeding by promoting the inner diameter and muscle development of the pharynx and oesophagus in zebrafish ( Danio rerio ) larvae - Shulin Tang; Xu‐Fang Liang; Shan He; Muhammad Shoaib Alam; Haocan Luo; Yulan Kuang (Journal of Fish Biology, 2020)
Activin A belongs to the superfamily of transforming growth factor‐β and plays an important role in hormone regulation and tissue development. However, few research studies have been conducted on the effect of activin A on feeding organs in fish. In this study, the zebrafish ( Danio rerio ) larvae were treated with 1 ng ml –1 activin A for 8 days continuously. The haematoxylin and eosin (H&E) staining section results revealed that the transverse inner diameter of the pharynx and oesophagus significantly increased on the third and eighth days after treatment compared with the control group ( P 2 compared to the control group ( P in situ hybridization results also showed that the expression of skeletal muscle‐specific genes ( myog and myod ) was significantly increased in pharyngeal muscle on the eighth day. Furthermore, the qRT‐PCR results showed the expression of gh gene was significantly increased on the eighth day ( P Artemia ) than in the control group on the eighth day. In conclusion, activin A could affect feeding by promoting the inner diameter and muscle development of the pharynx and oesophagus in zebrafish larvae. This study is the first to report that the development of the pharynx and oesophagus can directly affect food intake in fish larvae, which provides a theoretical basis for the study of food intake of fish at an early stage.

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Vicissitudes experienced by the oldest urban center in Bangladesh in relation to the migration of the Brahmaputra River - Gang Hu; Ping Wang; Sufi Mostafizur Rahman; Dehong Li; Muhammad Mahbubul Alam; Jiafu Zhang; Zhengyao Jin; Anchuan Fan; Jie Chen; Aimin Zhang; Wenqing Yang (Journal of Quaternary Science, 2020)
Bangladesh is one of the most densely populated countries in the world. There are 57 trans‐frontier rivers in the country, the widest being the Brahmaputra River. The river's channels have frequently changed course, but the relationship between such river migrations and human settlement patterns has remained unstudied. In this paper, optically stimulated luminescence and radiocarbon dating techniques were applied to sedimentary and organic materials in the oldest urban center (Wari‐Bateshwar) in Bangladesh. The results showed that the landscape around the urban center was dominated by floodplain and peatland facies between 7.9–7.6 and 4.7–1.6 ka, respectively. Humans occupied this area at ~3.2 ka, and manufactured delicate semi‐precious gemstone beads between ~2.4 and 1.8 ka. The urban center might be the same as an important city of the Gangaridai described in historical records. Due to fluvial migration at ~1.8 ka, the area surrounding the urban center was covered by fluvial sand. Humans might have been forced to abandon the urban center, leading to the bead processing technology in Bangladesh being lost forever.

Heavy Metals Assessment in Water, Sediments, Algae and Two Fish Species from River Swat, Pakistan - Israr Alam; Muhammad Nasir Khan Khattak; Shahi Mulk; Farman Ullah Dawar; Lubna Shahi; Ihsanullah Ihsanullah (Bulletin of Environmental Contamination and Toxicology, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

Climate change–induced human conflicts and economic costs in Pakistani Punjab - Khuda Bakhsh; Karim Abbas; Sarfraz Hassan; Muhammad Asim Yasin; Rafaqet Ali; Najid Ahmad; Muhammad Waqas Alam Chattha (Environmental Science and Pollution Research, 2020)

Salivary Proteomic Analysis of Betel Nut (Areca catechu) Consumers by Mass Spectrometry Revealed Primary Indication of Oral Malignancies - Rabia Sultan; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Mehtab Alam; Ikram-ul Haque (International Journal of Peptide Research and Therapeutics, 2020)

Transferability of object-based image analysis approaches for landslide detection in the Himalaya Mountains of northern Pakistan - Alam Sher Bacha; Harald Van Der Werff; Muhammad Shafique; Hawas Khan (International Journal of Remote Sensing, 2020)

Composition and source apportionment of saccharides in aerosol particles from an agro-industrial zone in the Indo-Gangetic Plain - Muhammad Usman Alvi; Magdalena Kistler; Imran Shahid; Khan Alam; Farrukh Chishtie; Tariq Mahmud; Anne Kasper-Giebl (Environmental Science and Pollution Research, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

The Ameliorative Role of 5-Aminolevulinic Acid (ALA) Under Cr Stress in Two Maize Cultivars Showing Differential Sensitivity to Cr Stress Tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Bilal Hussain; Afzal Hussain; Pravej Alam; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi AbdAllah (Journal of Plant Growth Regulation, 2019)

The dirty energy dilemma via financial development and economic globalization in Pakistan: new evidence from asymmetric dynamic effects - Muhammad Tariq; Yingzhi Xu; Faqeer Muhammad; Khalid Mehmood Alam (Environmental Science and Pollution Research, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

Haunch retrofitting technique for seismic upgrading deficient RC frames - Naveed Ahmad; Junaid Akbar; Muhammad Rizwan; Bashir Alam; Akhtar Naeem Khan; Abdul Lateef (Bulletin of Earthquake Engineering, 2019)

Melatonin Rescue Oxidative Stress-Mediated Neuroinflammation/ Neurodegeneration and Memory Impairment in Scopolamine-Induced Amnesia Mice Model - Tahir Muhammad; Tahir Ali; Muhammad Ikram; Amjad Khan; Sayed Ibrar Alam; Myeong Ok Kim (Journal of Neuroimmune Pharmacology, 2019)

Natural disasters and Malaysian economic growth: policy reforms for disasters management - Muhammad Imran Qureshi; Rosman Md. Yusoff; Sanil S. Hishan; ASA Ferdous Alam; Khalid Zaman; Amran Md. Rasli (Environmental Science and Pollution Research, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Effect of Nelumbo nucifera fruit on scopolamine induced memory deficits and motor coordination - Rafeeq Alam Khan; Muhammad Ali Rajput; Tahira Assad (Metabolic Brain Disease, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Foliar- and soil-applied salicylic acid and bagasse compost addition to soil reduced deleterious effects of salinity on wheat - Muhammad Imran Khan; Muhammad Aqeel Shoukat; Sardar Alam Cheema; Shafaqat Ali; Muhammad Azam; Muhammad Rizwan; Rashad Qadri; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2019)

A novel homozygous mutation in SZT2 gene in Saudi family with developmental delay, macrocephaly and epilepsy - Muhammad Imran Naseer; Mohammad Khalid Alwasiyah; Angham Abdulrahman Abdulkareem; Rayan Abdullah Bajammal; Carlos Trujillo; Muhammad Abu-Elmagd; Mohammad Alam Jafri; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2018)

Impact of maturity on phenolic composition and antioxidant activity of medicinally important leaves of Ficus carica L. - Muhammad Nadeem; Alam Zeb (Physiology and Molecular Biology of Plants, 2018)

Concentrations, dietary exposure, and human health risk assessment of heavy metals in market vegetables of Peshawar, Pakistan - Mehboob Alam; Maaz Khan; Anwarzeb Khan; Shah Zeb; Muhammad Amjad Khan; Noor ul Amin; Muhammad Sajid; Abdul Mateen Khattak (Environmental Monitoring and Assessment, 2018)

Effect of Trigonella foenum-graecum Linn. seeds methanol extract on learning and memory - Tahira Assad; Rafeeq Alam Khan; Muhammad Ali Rajput (Metabolic Brain Disease, 2018)

Landslide inventory and susceptibility modelling using geospatial tools, in Hunza-Nagar valley, northern Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff (Journal of Mountain Science, 2018)

Socio-demographic characters, distribution and transformation of iodine in soil, plant and wheat grains at District Diamer, Gilgit-Baltistan, Pakistan - Faridullah; Didar Ahmad; Hina Shabbir; Toqeer Ahmed; Muhammad Irshad; Arif Alam; Asif Sardar (Environmental Geochemistry and Health, 2018)

Modification of Osmolytes and Antioxidant Enzymes by 24-Epibrassinolide in Chickpea Seedlings Under Mercury (Hg) Toxicity - Parvaiz Ahmad; Mohammad Abass Ahanger; Dilfuza Egamberdieva; Pravej Alam; Mohammed Nasser Alyemeni; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Antifungal exploitation of fungicides against Fusarium oxysporum f. sp. capsici causing Fusarium wilt of chilli pepper in Pakistan - Muhammad Rizwan Bashir; Muhammad Atiq; Muhammad Sajid; Muhammad Mohsan; Waseem Abbas; Muhammad Waqar Alam; Muhammad Bashair (Environmental Science and Pollution Research, 2018)

Current status and future possibilities of molecular genetics techniques in Brassica napus - Muhammad Afzal; Salem Safer Alghamdi; Muhammad Habib ur Rahman; Awais Ahmad; Tahir Farooq; Mukhtar Alam; Imtiaz Ali Khan; Hidayat Ullah; Wajid Nasim; Shah Fahad (Biotechnology Letters, 2018)

Anti-epileptic activity of Nelumbo nucifera fruit - Muhammad Ali Rajput; Rafeeq Alam Khan; Tahira Assad (Metabolic Brain Disease, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

A long-term trend in precipitation of different spatial regions of Bangladesh and its teleconnections with El Niño/Southern Oscillation and Indian Ocean Dipole - Md. Kawser Ahmed; Mohammad Samsul Alam; Abu Hena Muhammad Yousuf; Md. Monirul Islam (Theoretical and Applied Climatology, 2017)

Phytochemical screening, acute toxicity, anxiolytic and antidepressant activities of the Nelumbo nucifera fruit - Muhammad Ali Rajput; Rafeeq Alam Khan (Metabolic Brain Disease, 2017)

Eco-Friendly Synthesis of Silver Nanoparticles Through Economical Methods and Assessment of Toxicity Through Oxidative Stress Analysis in the Labeo Rohita - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Asghar; Muhammad Shakeel; Muhammad Fakhar -e -Alam (Biological Trace Element Research, 2017)

Pathogenic diversity of Xanthomonas oryzae pv. oryzae isolates collected from Punjab Province of Pakistan - Hafiz Muhammad Imran Arshad; Kamran Saleem; Junaid Ahmed Khan; Muhammad Rashid; Muhammad Atiq; Syed Sarwar Alam; Shahbaz Talib Sahi (European Journal of Plant Pathology, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

RETRACTED ARTICLE: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2016)

Surfactant enhanced pyrene degradation in the rhizosphere of tall fescue (Festuca arundinacea) - Sardar Alam Cheema; Muhammad Imran Khan; Xianjin Tang; Chaofeng Shen; Muhammad Farooq; Yingxu Chen (Environmental Science and Pollution Research, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Molecular docking and inhibition studies on the interactions of Bacopa monnieri’s potent phytochemicals against pathogenic Staphylococcus aureus - Talha Bin Emran; Md Atiar Rahman; Mir Muhammad Nasir Uddin; Raju Dash; Md Firoz Hossen; Mohammad Mohiuddin; Md Rashadul Alam (DARU Journal of Pharmaceutical Sciences, 2015)

Use of statistical and GIS techniques to assess and predict concentrations of heavy metals in soils of Lahore City, Pakistan - Nayab Alam; Sajid Rashid Ahmad; Abdul Qadir; Muhammad Imran Ashraf; Calvin Lakhan; V. Chris Lakhan (Environmental Monitoring and Assessment, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Triarylimidazoles-synthesis of 3-(4,5-diaryl-1H-imidazol-2-yl)-2-phenyl-1H-indole derivatives as potent α-glucosidase inhibitors - Sadia Naureen; Shazia Noreen; Areesha Nazeer; Muhammad Ashraf; Umber Alam; Munawar Ali Munawar; Misbahul Ain Khan (Medicinal Chemistry Research, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Physiological and biochemical markers to optimize sugar mill wastewater for irrigation in maize (Zea mays L.) crop - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Abida Parveen; Rizwan Alam; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Observed damages in Pakistan due to 16 April 2013 Iran earthquake - Muhammad Masood Rafi; Sarosh H. Lodi; Muhammad Ahmed; Naveed Alam (Bulletin of Earthquake Engineering, 2015)

Variability of aerosol optical depth over Swat in Northern Pakistan based on satellite data - Khan Alam; Rehana Khan; Shahid Ali; Muhammad Ajmal; Gulzar Khan; Wazir Muhammad; Malak Azmat Ali (Arabian Journal of Geosciences, 2015)

Mitochondrial Ca2+ uniporter (MCU)-dependent and MCU-independent Ca2+ channels coexist in the inner mitochondrial membrane - Alexander I. Bondarenko; Claire Jean-Quartier; Warisara Parichatikanond; Muhammad Rizwan Alam; Markus Waldeck-Weiermair; Roland Malli; Wolfgang F. Graier (Pflügers Archiv - European Journal of Physiology, 2014)

Breeding approaches for bacterial leaf blight resistance in rice (Oryza sativa L.), current status and future directions - Mueen Alam Khan; Muhammad Naeem; Muhammad Iqbal (European Journal of Plant Pathology, 2014)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

A Battery of Bioassays for the Evaluation of Phenanthrene Biotoxicity in Soil - Muhammad Imran Khan; Sardar Alam Cheema; Xianjin Tang; Muhammad Zaffar Hashmi; Chaofeng Shen; Joonhong Park; Yingxu Chen (Archives of Environmental Contamination and Toxicology, 2013)

In silico analysis reveals the presence of a large number of Ankyrin repeat containing proteins in Ectocarpus siliculosus - Niaz Mahmood; Mahdi Muhammad Moosa; Nahid Tamanna; Suprovath Kumar Sarker; Rifat Ara Najnin; Salma Sultana Alam (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Biotoxicity Assessment of Pyrene in Soil Using a Battery of Biological Assays - Muhammad Imran Khan; Sardar Alam Cheema; Xianjin Tang; Chaofeng Shen; Shahbaz Talib Sahi; Abdul Jabbar; Joonhong Park; Yingxu Chen (Archives of Environmental Contamination and Toxicology, 2012)

Assessment of phenanthrene bioavailability in aged and unaged soils by mild extraction - Muhammad Imran Khan; Sardar Alam Cheema; Chaofeng Shen; Congkai Zhang; Xianjin Tang; Jiyan Shi; Xincai Chen; Joonhong Park; Yingxu Chen (Environmental Monitoring and Assessment, 2012)

Evaluating surface drying and re-drying for wheat seed priming with polyamines: effects on emergence, early seedling growth and starch metabolism - Muhammad Farooq; Tariq Aziz; Hafeez ur Rehman; Atique ur Rehman; Sardar Alam Cheema; Tariq Aziz (Acta Physiologiae Plantarum, 2011)

Assessment of Pyrene Bioavailability in Soil by Mild Hydroxypropyl-β-Cyclodextrin Extraction - Muhammad Imran Khan; Sardar Alam Cheema; Chaofeng Shen; Congkai Zhang; Xianjin Tang; Zaffar Malik; Xincai Chen; Yingxu Chen (Archives of Environmental Contamination and Toxicology, 2011)

A Putative Leucine-Rich Repeat Receptor-Like Kinase of Jute Involved in Stress Response - Md. Maksudul Alam; Sazia Sharmin; Zinnatun Nabi; Shakhinur Islam Mondal; Md. Shahidul Islam; Sarmah Bin Nayeem; Muhammad Shoyaib; Haseena Khan (Plant Molecular Biology Reporter, 2010)

Response of three wheat genotypes grown under saline medium to low/high potassium levels - M. U. Shirazi; B. Khanzada; Muhammad Ali; Ejaz ul Islam; S. M. Mujtaba; R Ansari; S. M. Alam; M. A. Khan; Mukhtiar Ali (Acta Physiologiae Plantarum, 2002)